ANALISIS PELAKSANAAN PENGAWASAN PENGENAAN PAJAK PENGHASILAN ATAS PENGHASILAN YOUTUBERS PADA DIREKTORAT JENDERAL PAJAK TAHUN 2018 - Ainul Dian Lestari; Safri Nurmantu; Resista Vikaliana (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2019)
The phenomenon of technological development at this time resulted in many types of new jobs that have sprung up. The new types of work include programmers, and YouTubers. Both types of work each use a different social media platform for their work media. If a celebgram uses Instagram, Youtuber uses YouTube as a creative platform for his work.Based on this, the study would like to know the process of implementation of supervision carried out by the Directorate General of Taxes in overseeing the potential income tax arising from the income of Google AdSense. In detail, the purpose of this study is to analyze the implementation of the supervision of income taxation on adsense income received by Youtubers, analyze the inhibiting entities that are simultaneously interrelated with the implementation of the supervision of the imposition of income tax youtubers, as well as analyze the driving entities that are simultaneously interrelated with the implementation of the imposition of supervision YouTubers income tax. The study was conducted with a qualitative approach. Informants consist of the Directorate of Potential Compliance and Tax Revenue/ PKP Directorate, 2 (two) Youtubers, in this case the intended Youtuber is a YouTuber who has received income from Google Adsense and 1 (one) Academic Lecturer. Data were analyzed using the Huberman Miles Model.The results showed that the supervision process carried out by the Directorate General of Taxes in order to monitor the potential tax arising from adsense income is not effective. Simultaneous inhibiting entities that are interrelated with the implementation of supervision over the imposition of income tax on income of the youtubers is that the Directorate of Potential Compliance and Tax Revenue/ PKP Directorate does not have the overall Taxpayer Youtuber data, so that the identification of WP youtuber compliance is not comprehensive and the AdSense revenue calculation scheme conducted by Google is unknown to the PKP Directorate . The Supporting Entity is simultaneously interrelated with the implementation of the supervision of the imposition of income tax on income of youtubers is to socialize the imposition of income tax arising from adsense income to the youtubers and follow up on cooperation with Google from the regulatory channel..